Power to the package. - Herrell, D.
Electronic packaging technology focuses on where and how the silicon IC is connected into the electronic system. That makes a package the meeting place of a number of tradeoffs, whose constraining influence on what might and might not change will largely determine how the technology of the year 2003 will develop. Here, the author describes how ball-grid array technology seems to offer the compactness, high input/output count and high-speed compatibility required for the next few years
Keywords: Ball-grid array technology; Electronic packaging technology; High-speed compatibility; Input/output count; Silicon IC